M-Learning Using Mobile Learning Engine - Abas, Noorfaizah (Universiti Teknologi Petronas, 2006)
The objective of M-Learning is to integrate the technology combined with the education in order to enhance the effectiveness of student's traditional learning process. In order to explore the use of mobile and handheld IT devices as a learning tool, many factors need to be considered such as its constraint and limitations. Therefore, intensive researches need to be done. The main purpose of M-Learning is to create flexible learning environment for students where the implementation of just-in-time learning is applied. Besides, it creates new approach of learning style. The most challenging part in implementing MLearning is in delivering the content as how users will view the materials in mobile devices instead of the usual large screen desktops. Apart from that, the technology of M-Learning is still new in Malaysia, therefore, a lot of risk and challenges involved in this project. Meanwhile, the target user is students. In this project the methodology used follows four processes which are planning, analysis, design and implementation. Efficiency and flexibly together with ease ofuse become the essential elements inconstructing the final system.